Analysis of fishing data in Pernambuco, Sergipe and Bahia: Focus on reports of crimes against endangered turtles (Research, Society and Development, 2024)
This study carries out a comparative analysis of data relating to fishing crimes in the states of Pernambuco, Sergipe, and Bahia, located in Brazil. The research is based on information from inspection reports and incident records. The main objective is to identify patterns and trends related to fishing crimes. A comprehensive analysis of the data reveals the extent of the fishing crime problem in these coastal and river states. Furthermore, the seasonality of these crimes stands out, with accentuated occurrences in certain annual periods. The research also allows identifying areas with the highest concentration of these infractions. Additionally, specific patterns of transgressions emerge, such as the detection of the illicit use of fishing equipment and the capture of threatened species, such as turtles. The insights extracted from this analysis provide essential information for the development of strategies and policies aimed at combating fishing crimes in these states. In this way, research based primarily on data from the Biodiversity Portal and Global Fish Watching, analyzed through the main Python libraries, contributes to the preservation of fishing resources and the safeguarding of marine and river ecosystems, especially in the Fernando de Noronha region, where reports of crimes against endangered turtles are of particular concern.